2021
DOI: 10.1108/amhid-06-2020-0014
|View full text |Cite
|
Sign up to set email alerts
|

Exploring how to deliver videoconference-mediated psychological therapy to adults with an intellectual disability during the coronavirus pandemic

Abstract: Purpose The novel coronavirus and associated restrictions have resulted in mental health services across the UK having to adapt how they deliver psychological assessments and interventions. The purpose of this paper is to explore the accessibility and prospective acceptability of providing telephone and videoconference-mediated psychological interventions in individuals with intellectual disabilities. Design/methodology/approach As part of a service evaluation, a mixed-methods questionnaire was developed and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 25 publications
0
43
0
Order By: Relevance
“…However, there is a relative dearth of research assessing the feasibility and effectiveness of video conferencing amongst people with mild intellectual disabilities (Oudshoorn et al 2021). Recently, in a small-scale mixed-methods study, Rawlings et al (2020) explored the accessibility and acceptability of using video conferencing for psychological interventions for anxiety, low mood and anger amongst people with intellectual disabilities, and found that only a minority of service users accepted therapy being conducted in this way. Given that professionals play a key role in the acceptance and implementation of interventions delivered by a broad range of eHealth applications, such as video conferencing (Henneman et al 2017), it is important to also explore their perspectives.…”
mentioning
confidence: 99%
“…However, there is a relative dearth of research assessing the feasibility and effectiveness of video conferencing amongst people with mild intellectual disabilities (Oudshoorn et al 2021). Recently, in a small-scale mixed-methods study, Rawlings et al (2020) explored the accessibility and acceptability of using video conferencing for psychological interventions for anxiety, low mood and anger amongst people with intellectual disabilities, and found that only a minority of service users accepted therapy being conducted in this way. Given that professionals play a key role in the acceptance and implementation of interventions delivered by a broad range of eHealth applications, such as video conferencing (Henneman et al 2017), it is important to also explore their perspectives.…”
mentioning
confidence: 99%
“…Others may necessitate systemic approaches [ 50 ], thus the approach outlined in this case study may not be widely replicable. Rawlings et al [ 58 ] also support this view, reporting that the majority of PWID were unable to participate in video therapy during COVID-19.…”
Section: Discussionmentioning
confidence: 94%
“…This lack of data could further contribute to health-care inequalities in people who have ID, reported prior to (Beail, 2016a) and during the pandemic (Iacobucci, 2021). Moreover, the available evidence suggests that less than onethird of people with ID referred to adult ID community health service (n = 22) were accepting of remote psychological therapies during the pandemic, with the majority not interested or unable to receive therapy via videoconference due to technology accessibility issues (Rawlings et al, 2021). The Division of Clinical Psychology, Faculty for People with ID published guidance in May 2020, during the pandemic, on how to meet the psychological needs of people with ID (British Psychological Society, 2020).…”
Section: Introductionmentioning
confidence: 99%